RECESSION OF KAFFIØYRA REGION GLACIERS, OSCAR II LAND, SVALBARD - Sobota, Ireneusz; Lankauf, Krzysztof R. (Bulletin of Geography. Physical Geography Series, 2010)
The main aim of this research was to describe the course of the glacier retreat in the Kaffiøyra Region, starting from the maximum advance of the glaciers to the year 2009. From maps and archival data as well as the results of the field measurements and GPS measurements carried out in the years 1977–2009, the authors present the retreat histories for six glaciers. The smallest retreat was recorded for Waldemarbreen (8 m a-1), while Elisebreen retreated at the fastest rate of 18 m a-1. Since 1909 the area of Kaffiøyra glaciers has decreased by 37% on average. The smallest change was recorded in the case of Irenebreen and Waldemarbreen, while the largest was in the case of Oliverbreen and Einvindbreen. As the analysis of the glacier extension in the valley areas of the Kaffiøyra Region indicates, all of them have been in the same recession stage since 1909.